Peran Digital Payment dalam Efisiensi Keuangan Usaha Mikro di Kota Semarang - Ginanjar Suendro; Ericke Fridatien (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the role of digital payment in improving financial efficiency among micro-enterprises in Semarang City. The advancement of financial technology provides faster, easier, and more transparent transaction alternatives, which have the potential to enhance financial management for business actors. This research adopts a quantitative approach using a survey method involving 100 micro-business owners who have implemented digital payment systems such as QRIS, e-wallets, and mobile banking. The results show that digital payment usage significantly affects financial efficiency, as evidenced by improved financial record-keeping, better cash flow management, and reduced transaction costs. These findings highlight the importance of adopting digital financial technology as a strategy to enhance financial performance, especially for micro-enterprises in Semarang City.